RANTAI NILAI (VALUE CHAIN) AGRIBISNIS LABU DI KECAMATAN GETASAN KABUPATEN SEMARANG - Kusumawati, Agni; Santosa, Purbayu Budi (Diponegoro Journal of Economics, 2013)
This study aims to explore the value chain of pumpkins farming to improve the pumpkin agribusiness performance in Getasan region of Semarang,Central Java. Pumpkin agribusiness is remain as a seconday job farmers in the study area, where as the main corps among others are tobacco, chili, vegetable, etc. Sampling method of quoted purposive sample has been invoked to select 60 farmers. While, the in-depth interview had been done with the stakeholders of academician, government, business and community (A-G-B-C). The results showed that the most benefited in the pumpkin chain is retailers. On the other hand, farmers were less to have benefit from pumpkin agribusiness. This Â mightbe due to farmers acted as the price taker. Therefore, it is indeed need to improve the agribusiness chain in pumpkin farming.